Forecasting risk measures based on structural breaks in the correlation matrix - Fang Duan (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
Correlation models, such as Constant Conditional Correlation (CCC) GARCH model or Dynamic Conditional Correlation (DCC) GARCH model, play a crucial role in forecasting Value-at-Risk (VaR) or Expected Shortfall (ES). The additional inclusion of constant correlation tests into correlation models has been proven to be helpful in terms of the improvement of the accuracy of VaR or ES forecasts. Galeano & Wied (2017) suggested an algorithms for detecting structural breaks in the correlation matrix whereas Duan & Wied (2018) proposed a residual based testing procedure for constant correlation matrix which allows for time-varying marginal variances. In this chapter, we demonstrate the application of aforementioned correlation testing procedures and compare its performance in backtesting VaR and ES predictions. Portfolios in consideration are constructed from four stock indices DAX30, STOXX50, FTSE100 and S&P500. – – Korrelationsmodelle, z.B. GARCH-Modell der konstanten bedingten Korrelation (CCC) oder das GARCH-Modell der dynamischen bedingten Korrelation (DCC), spielen eine entscheidende Rolle bei der Vorhersage des Value-at-Risk (VaR) oder des Expected Shortfall (ES). Die zusätzliche Einbeziehung von konstanten Korrelationstests in Korrelationsmodelle hat sich als hilfreich erwiesen, um die Genauigkeit von VaR- oder ES-Vorhersagen zu verbessern. Galeano & Wied (2017) schlugen einen Algorithmus zur Erkennung von Strukturbrüchen in der Korrelationsmatrix vor, während Duan & Wied (2018) ein auf Residuen basierendes Testverfahren für eine konstante Korrelationsmatrix vorschlugen, das zeitvariable marginale Varianzen berücksichtigt. In diesem Kapitel demonstrieren wir die Anwendung der vorgenannten Korrelations-Testverfahren und vergleichen ihre Leistung beim Backtesting von VaR- und ES-Vorhersagen. Die betrachteten Portfolios werden aus den vier Aktienindizes DAX30, STOXX50, FTSE100 und S&P500 gebildet.
Keywords: C12; C32; C53; C58; 330; structural break tests; correlation model; value-at-risk; expected shortfall